1871 Ky. Acts 89 - (:unkn) unknown (My University, 1871)
Act to Prohibit the Carrying of Concealed Deadly Weapons, ch. 1888,§ 1-2, 5: That if any person shall hereafter carry concealed any deadly weapon upon their persons other than an ordinary pocket-knife, except as provided for in next section, he shall be fined, on the first conviction, not less than twenty-five dollars nor more than one hundred dollars, or imprisoned not less than thirty days nor more than sixty days, or both so fined and imprisoned; and on any subsequent conviction not less than one hundred nor more than four hundred dollars, or imprisoned not less than two months nor more than six months, or both.
Keywords: CARRY - CONCEALED